(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article deeply analyzes the historical, economic, social, and architectural significance of the Central Asian sardobas (water reservoirs/cisterns) located along the Great Silk Road (GSR). Since the GSR was the main artery of trade, culture, and inter-civilizational dialogue, securing water supply in desert and semi-desert conditions played a crucial role in the continuous movement of caravans and the stability of trade activities. Sardobas were not just hydro-technical structures but also served as rest stops for caravans, defense points, and a source of life for surrounding settlements. The research examines the water storage technology, placement of the sardobas, and their contribution to the sustainable development of the GSR, based on medieval sources, archaeological data, and existing scientific literature.